How Capital Adequacy Ratio, Non-Performing Loans and Good Corporate Governance Affect Company Value with Financial Performance as Intervening Variables : (Empirical Study of Commercial Banks Registered On the Idx for the 2017-2019 Period) - Rifani Akbar Sulbahri; Luk Luk Fuadah; Yulia Saftiana; Sa'adah Sidiq (International Journal of Economics and Management Research, 2023)
The increasingly open economic system between countries, known as international trade, is evidence of the rapid expansion of the current economic system. The only depository financial institution is a bank. In this study, we will discuss how Capital Adequacy Ratio, Non-Performing Loans and Good Corporate Governance Affect Firm Value with Financial Performance as an Intervening Variable. Data analysis techniques use descriptive analysis, panel data regression estimation, common effect models, fixed effect models, random effect models, Chow tests, Hausman tests, Lagrange Multiplier tests, classical assumption tests (normality tests, multicollinearity tests, heteroscedasticity tests). Hypothesis test (F test and T test). This study is a quantitative study through an analytical descriptive study, seen from the characteristics of the problems studied. The population of this study are commercial banks listed on the Indonesia Stock Exchange in 2017 and 2019. The results show the effect of the variables capital adequacy ratio, non-performing loans, good corporate governance and return on assets on company value shown to show that the prob. F (Statistic) of 0.0160 is smaller than the significance level of 0.05. This means that the capital adequacy ratio, non-performing loans, good corporate governance and intervening return on assets variables simultaneously affect firm value in banking companies.